Developing Interactive Listening Comprehension Materials in Self-Learning Center (Slc) For the Students At Iain Kediri - Fakrurriana Fakrurriana (LPPM IAI Hasanuddin Pare-Kediri, 2019)
This research and development (R&D) study is conducted to develop Interactive Listening Comprehension Materials in Self-Learning Center (SLC) for the Students at State Islamic Institutes (IAIN) Kediri. The research involves the students of basic level of the university students, SLC advisor, and four experts. The instruments in needs survey consist of questionnaires, an interview guide, and field notes. The data from the students is calculated in percentage and those from the SLC advisor and from the field notes are described in qualitative way. The data from needs survey is used as the basis for the materials development. A validation form is used to collect the experts’ judgment on the materials. The experts validate the materials in terms of the program and the content of language. The data from the experts are analyzed in percentage and also described qualitatively